Effect of cavity parameters on the fire dynamics of ventilated façades. (October 2022) - Mendez, Julian E.; Lange, David; Hidalgo, Juan P.; McLaggan, Martyn S.
Abstract: Narrow gaps and cavities present in modern construction systems have been identified as one of the key elements that may enable fire spread after an initial fire ignition. Although there are existing models to predict the exposure of the inner linings of a cavity when exposed to a fire, these models have a significant amount of error or are limited to small ranges of application. A parametric experimental study was performed to characterise the fire dynamics in a cavity using a medium-scale non-combustible parallel wall testing rig. Three different cavity widths, three different heat release rates and two air entrainment conditions at the base of the setup (i.e. closed, with no air entrainment at the base; open, with unrestricted air entrainment at the bottom) were varied. Measurements of the flame height and the total external heat flux on the cavity walls were performed. It has been shown that both the heat fluxes and the flame heights increased as the cavity width was reduced. It was found that the radiative component dominates the heat transfer at the bottom of the setup and is less relevant as the height increases, the cavity width increases and the burner output is reduced. Correlations were developed to quantify the heat exposure of a cavity as a function of the geometry of the system, the size of the fire and the ventilation condition. The results obtained can be further used as a baseline in the modelling of upward flame spread in confined spaces featuring combustible linings, and for assessing the potential risks of ignition of combustible elements in ventilated façade systems.